Women’s Professional Career through Al-Qur’an’s Persepectives - Saleh, Muhamad (International Journal Labs, 2022)
Women's careers are still a constant topic discussed. As if a career becomes an expensive thing for women, especially women who still want to devote themselves to the family, for this type of woman, a career really becomes an expensive item. To find out how the meaning of women's professional career in the perspective of the Qur'an, the opinions of commentators and feminists regarding careers women's professionals in the perspective of the Qur'an, the history of women's professional careers from the time of the Prophet to modern times, and the meaning of leadership in the family (Domestic-public) related to women's professional careers in the perspective of the Qur'an. Judging from the purpose of this research, it is an expolative research which is still included in the category of qualitative approach. Data collection was carried out by browsing commentaries, books, both primary and secondary which were relevant to the discussion of the research theme. This study analyzes the substance of the mufassir's thoughts on the concept of the creation of air in the Qur'an and then draws it on the present context. Meanwhile, to analyze the data with certain words and terms from the verses of the Qur'an. It is true that Islam forbids women from pursuing careers outside the home but neglecting their responsibilities as housewives. Prioritizing a career in order to pursue a life that exceeds its nature is actually contrary to the values of Islamic teachings.